Impact of vaccination in the reduction of hepatitis B in Paraná - Priscila PUDELCO; Andreia Eloize KOEHLER; Lúcia Helena Linheira BISETTO
This study identified the impact of hepatitis B vaccine over reducing incidence of this disease in Paraná State, between 2001 and 2011, and discussed the role of nursing in immunization. Descriptive documental and quantitative research. Utilized secondary data of hepatitis B, between 2001 and 2011 and vaccination coverage of hepatitis B vaccine between 1995 and 2011 in Paraná State, available in DATASUS, SINAN and Immunization Programs. Data has been collected from May to July 2012. Included cases of hepatitis B confirmed by laboratory testing. Of the 14,434 selected cases, 81,8% was in urban residents, 86,5% belonged to 20 to 59 age group and 45,3% were infected by sexual transmission. In the correlation of vaccine coverage with the incidence, was identified reducing this rate in the range of 0 to 9 years old, in places with vaccination coverage's above 95%. It concludes that hepatitis B vaccination had impact over disease reduction in Paraná State.